Awake tracheal intubation in a suspected COVID‐19 patient with critical airway obstruction. Issue 1 (4th May 2020) - Ahmad, I.; Wade, S.; Langdon, A.; Chamarette, H.; Walsh, M.; Surda, P.
Summary: We report the airway management of a patient with suspected COVID‐19 with impending airway obstruction requiring urgent surgical tracheostomy. To our knowledge, this is the first reported case of an awake tracheal intubation in a suspected COVID‐19–positive patient. Various modifications were put in place during the awake tracheal intubation and surgical tracheostomy procedures to minimise aerosol generation from the patient, such as avoiding high‐flow nasal oxygen, establishing conscious sedation with remifentanil before commencing airway topicalisation and avoiding transtracheal local anaesthetic infiltration. A multidisciplinary team discussion before performing the case highlighted aspects of both the airway management and the surgical procedure where particular care and modifications are required. There is a lack of national and international guidance for awake tracheal intubation and tracheostomy in COVID‐19 cases. This report nevertheless addresses the key procedural modifications required.